Reliability and Validity Measurement of Sagittal Lumbosacral Quiet Standing Posture with a Smartphone Application in a Mixed Population of 183 College Students and Personnel - George A. Koumantakis; Maria Nikoloudaki; Sara Thacheth; Kalliroi Zagli; Konstantina Bitrou; Andreas Nigritinos; Leon Botton (Advances in Orthopedics)
Accurate recording of spinal posture with simple and accessible measurement devices in clinical practice may lead to spinal loading optimization in occupations related to prolonged sitting and standing postures. Therefore, the purpose of this study was to establish the level of reliability of sagittal lumbosacral posture in quiet standing and the validity of the method in differentiating between male and female subjects, establishing in parallel a normative database. 183 participants (83 males and 100 females), with no current low back or pelvic pain, were assessed using the “iHandy Level” smartphone application. Intrarater reliability (3 same-day sequential measurements) was high for both the lumbar curve (ICC2,1: 0.96, SEM: 2.13°, and MDC95%: 5.9°) and the sacral slope (ICC2,1: 0.97, SEM: 1.61°, and MDC95%: 4.46°) sagittal alignment. Data analysis for each gender separately confirmed equally high reliability for both male and female participants. Correlation between lumbar curve and sacral slope was high (Pearson’s r=0.86, p<0.001). Between-gender comparisons confirmed the validity of the method to differentiate between male and female lumbar curve and sacral slope angles, with females generally demonstrating greater lumbosacral values (p<0.001). The “iHandy Level” application is a reliable and valid tool in the measurement of lumbosacral quiet standing spinal posture in the sagittal plane.